Teorie della percezione delirante e origine della psicosi - Bisconti, Paola (Il sogno della farfalla, 2022)
The aim of this article is to provide an historical overview on the concept of delusional perception proposed by different authors such as Jaspers, Matussek, Conrad, Schneider, Binswanger and Barison. As highlighted by the analysis carried out in this paper, the importance of this symptom is crucial to understand the origin of psychosis. The author of this article underlines how the paper written by the psychiatrist Massimo Fagioli in 1962 on the delusional perception represented a turning point for the comprehension of this symptom and a crucial step for the subsequent discovery of the annulment pulsion.